Szubjektív realitásunk formálásának és céljaink elérésének új aspektusai: a kvantumfizika, pszichológia és a teológia találkozása - KRASZNAY, Mónika (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2018)
New Aspects of the Forming of Our Subjective Reality and Aiming Our Goals: the Encounter of Quantum Physics, Psychology and Theology. We intend to deal with the area of the new science of the 20ᵗʰ century, about the world and human consciousness, and revolutionary new statements about the possibilities of interaction of them which theories and discoveries are also relevant to the theology. The findings were emerged by quantum physics place our existing knowledge about world, human conscience in entirely new lightning, pointing to the possibilities of forming our life more consciously, and the responsibility of human in relation to his life. For theology, pastoral psychology it inevitably raises questions of prayer, meditation, contemplation, the narrower and broader sense of faith, faith and belief systems, desires, goals to achieve mental, psychological (thoughts, visualization, self-emptying) aspects.